Ecological correlates of variable organ sizes and fat loads in the most northerly wintering shorebirds - Ruthrauff, D. R.; Dekinga, A.; Gill, R. E.; Summers, R. W.; Piersma, T. (Canadian Journal of Zoology, 2013)
Shorebirds at northern latitudes during the nonbreeding season typically carry relatively large lipid stores and exhibit an up-regulation of lean tissues associated with digestion and thermogenesis. Intraspecific variation in these tissues across sites primarily reflects differences in environmental conditions. Rock (Calidris ptilocnemis (Coues, 1873)) and Purple (Calidris maritima (Brunnich, 1764)) sandpipers are closely related species having the most northerly nonbreeding distributions among shorebirds, living at latitudes up to 61 degrees N in Cook Inlet, Alaska, and up to similar to 71 degrees N in northern Norway, respectively. Cook Inlet is the coldest known site used by nonbreeding shorebirds, and the region's mudflats annually experience extensive coverage of foraging sites by sea and shore-fast ice. Accordingly, Rock Sandpipers increase their fat stores to nearly 20% of body mass during winter. In contrast, Purple Sandpipers exploit predictably ice-free rocky intertidal foraging sites and maintain low (